Captains of the clouds [videorecording (DVD)] - Curtiz, Michael, 1886-1962; Cagney, James, 1899-1986; Morgan, Dennis, 1908-1994; Marshall, Brenda, 1915-1992 (Archive collection., 2007)
A group of bush pilots from Northern Canada feel their patriotic spirit roused during Winston Churchill's famous "Blood, sweat and tears" radio speech to pump up the British/Allied morale. They decide to enlist as pilots, only to find their age and attitude working against them. One of the pilots, Brian McLean, finds that his commander is the former boyfriend of his wife. To make matters worse, Brian needs to do things his way, leading to a tragedy from which he must redeem himself.